Caracterização físico-química, microbiológica e de compostos bioativos de amostras de mel de Apis mellifera L. do Oeste do Paraná, Sul do Brasil - Galhardo, Douglas (2018)
The honey produced in the west region of Paraná, due to its physical-chemical qualities and the agro-industry organization, which involves its processing and commercialization, obtained the seal of Indication of Provenance. The objective of this study was to characterize the physicochemical characterization, phenolic compounds, antioxidant activity and the microbiological quality of 67 honey samples of Apis mellifera collected in 14 municipalities located in the West region of the state of Paraná, southern Brazil. The physico-chemical analyzes were: moisture, pH, hydroxymethylfurfural, acidity, protein, ashes, total sugars, reducing sugars, sucrose, color, electrical conductivity and also the total phenol, flavonoids and antioxidant activity were evaluated. FRAP, ABTS and DPPH. Microbiological quality was evaluated by counting coliforms at 35ºC and at 45ºC, mesophilic aerobic bacteria, Clostridium spp., total counts of molds and yeasts. The minimum and maximum values, medians, means and quartiles were calculated. The use of non-metric multidimensional scaling (NMDS) was used to test the differences of the parameters between different samples of honey. The microbiological quality of the analyzed honey samples presented adequate values for human consumption. Five genus of mold were isolated: Cladosporium spp., Phoma spp., Aspergillus spp., Fusarium spp. and Penicillium spp., commonly found in honey. The physico-chemical evaluations were mostly within the specifications determined by national and international legislation. The mean values were 18.75% for moisture, pH of 3.26, HMF of 10.79 mg.kg-1, acidity of 34.54 meq.kg-1, protein content of 0.28%, ash of 0.14%, total sugars of 69.09%, reducing sugars of 64.57%, sucrose of 4.28%, and 340.10 μS.cm-1 for conductivity. The color on the Pfund scale showed 0.26 mm, with a predominance of lighter shades, which favors the acceptability and commercialization of honey produced in the region. The total phenolic compounds were analyzed by Folin-Ciocalteu and flavonoids by the complexation method with aluminum chloride, with a mean content of 34.83 mgGAE.100 g-1 and 16.26 mgEQ.100 g-1, respectively. The antioxidant activity of honey samples presented a mean value of 0.12 μmolET. g-1 for DPPH of 1.01 μmolET. g-1 ABTS +, and 2.68 μmolSFE. g-1 for FRAP. The analyzes presented the formation of two groups for microbial evaluation, with a large group with 64 samples and one isolated group, highlighting the total coliform values. In relation to the physical-chemical parameters, bioactive compounds and antioxidant activity, the analysis verified the formation of nine groups, behaving similarly in relation to some parameters. The evaluations showed that the samples of the municipalities evaluated presented great similarity. These results are important to confirm the quality of the honey produced in the West of Paraná